2015
DOI: 10.18410/jebmh/2015/88
|View full text |Cite
|
Sign up to set email alerts
|

ATTITUDE AND PERCEPTION OF FACULTIES TOWARDS TEACHING EVIDENCE BASED MEDICINE TO PRE - CLINICAL & PARA - CLINICAL MEDICAL STUDENTS

Abstract: Evidence-based medicine (EBM) is defined as the "conscientious, explicit, and judicious use of current best evidence". It is an important tool for lifelong learning in medicine, and medical students can develop the skills necessary to understand and use EBM. The teaching of EBM in Sumandeep Vidyapeeth is as part of Evidence Based Education System (EBES). The university has implemented the 16 hours of teaching with project work on Evidence Based Medicine in 1st MBBS and 2nd MBBS curriculum in addition to MBBS s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…18 An Indian study in which Faculties teaching EBM were involved there was a consensus on EBM being important for ensuring a better clinical understanding of future clinical practice and its integration in undergraduate curriculum. 19 There are review articles from Pakistan. .At Shifa College of Medicine EBM is integrated in their academic activities like morning meetings and journal clubs.…”
Section: Wwwtheprofesionalcom Evidence Based Medicinementioning
confidence: 99%
“…18 An Indian study in which Faculties teaching EBM were involved there was a consensus on EBM being important for ensuring a better clinical understanding of future clinical practice and its integration in undergraduate curriculum. 19 There are review articles from Pakistan. .At Shifa College of Medicine EBM is integrated in their academic activities like morning meetings and journal clubs.…”
Section: Wwwtheprofesionalcom Evidence Based Medicinementioning
confidence: 99%
“…7 Patel B et al, studied "attitude of perception of faculties towards teaching evidence based medicine to pre-clinical & paraclinical medical students". 8 They found that, 83% of faculties agreed that they are interested in more learning and improving skills necessary to incorporate Evidence based medicine into their discipline.…”
Section: Outmentioning
confidence: 99%